Challenge Facing Sudanese Business Organizations For Using Knowledge Management System - Nour Eldin Mohamed, Elshaiekh; Peter Charles, Woods; Ahmed Ibrahim, Kashif (2008)
Challenge Facing Sudanese Business Organizations For Using Knowledge Management System